Standardized High-Resolution Ultrasound Protocol for the Diagnosis and Monitoring of Carpal Tunnel Syndrome: A Mixed-Design Observational Study - Fabiana Battaglia; Luigi Troisi; Emanuele Cigna; Francesco Stagno d’Alcontres; Vincenzo Rizzo; Gabriele Delia (Diagnostics)
Background/Objectives: Carpal tunnel syndrome (CTS) is a common entrapment neuropathy. Traditional diagnostics like EMG and NCSs are invasive and do not visualize nerve morphology. This study aims to evaluate the diagnostic and prognostic value of high-resolution ultrasonography in patients with CTS using a standardized scanning protocol and to evaluate the relationship between sonographic findings and traditional electrodiagnostic results. Methods: In this observational study with both prospective and retrospective components, 31 subjects were included. Between November 2023 and June 2024, 11 symptomatic CTS patients were scheduled for surgical decompression and 14 healthy controls were prospectively enrolled. Additionally, six post-surgical CTS patients who had undergone decompression between 2016 and 2021 were retrospectively included for comparative analysis. All underwent clinical and ultrasonographic assessments of the median nerve at predefined anatomical landmarks. EMG was performed in the CTS groups. Ultrasound was repeated at 1, 3, and 6 months postoperatively to monitor morphological changes. Results: CTS patients had significantly increased the median nerve CSA compared to controls. Postoperative ultrasound showed progressive CSA reduction correlating with clinical improvement and EMG recovery. The CSA correlated moderately to strongly with distal motor latency. Conclusions: High-resolution ultrasound is a reliable, non-invasive tool for diagnosing and monitoring CTS. Standardized protocols are needed to support broader clinical adoption and establish it as a standalone diagnostic method.